Uncovering The Importance Of Halal Toiletries: Determinant Factors Contributing Halal Toiletries’ Purchase Intention - Fiandari, Yulist Rima; Andharini, Sri Nastiti (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the products that needs to have halal label is toiletries. Toiletries are ranked as fourth halal product that receives attention so that they have huge potential to optimize. This research is needed to support the sustainability of halal industry especially toiletries product. This research is aimed at investigating the impact of halal awareness, attitude, subjective norms, perceived behavior control towards halal toiletries’ purchase intention. This study was conducted on 274 respondents through questionnaire as the research instrument. The research findings portrayed a significant impact of halal awareness, attitude, subjective norms, perceived behavior control towards halal toiletries’ purchase intention. Attitude played the role as the partial mediation between halal awareness and halal toiletries’ purchase intention.